The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/jawr.12085
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Future Climate Change Impact on Water Quality of Chungju Lake, South Korea, Using WASP Coupled with SWAT

Abstract: This study is to evaluate the future potential impact of climate change on the water quality of Chungju Lake using the Water Quality Analysis Simulation Program (WASP). The lake has a storage capacity of 2.75 Gm3, maximum water surface of 65.7 km2, and forest‐dominant watershed of 6,642 km2. The impact on the lake from the watershed was evaluated by the Soil and Water Assessment Tool (SWAT). The WASP and SWAT were calibrated and validated using the monthly water temperatures from 1998 to 2003, lake water quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 58 publications
(65 reference statements)
1
20
0
Order By: Relevance
“…Many studies have concluded that water temperature will increase because of global warming [2][3][4]36]. Our modelling results suggest that water temperature will increase between 2010 and either 2050 or 2080 with a corresponding decrease in ice thickness due to warmer air temperatures.…”
Section: Impact Of Increased Air Temperature On Water Qualitymentioning
confidence: 59%
“…Many studies have concluded that water temperature will increase because of global warming [2][3][4]36]. Our modelling results suggest that water temperature will increase between 2010 and either 2050 or 2080 with a corresponding decrease in ice thickness due to warmer air temperatures.…”
Section: Impact Of Increased Air Temperature On Water Qualitymentioning
confidence: 59%
“…Climate variability and hydrologic conditions have been shown to strongly impact biogeochemical processes in lakes and reservoirs (Adrian et al, 2009;Jeppesen et al, 2015;MacKay et al, 2009;Molina-Navarro et al, 2014). However, several recent modeling analyses have shown minimal DO responses to changes in climate, that is, Chesapeake Bay (Irby et al, 2016), South Umpqua River (Cox et al, 2015), and Chungju Lake (Park et al, 2013). No previous investigation has reported a modeling sensitivity analyses for the response of lake/reservoir DO to hydrologic variability using a mechanistic water quality model.…”
Section: Water Resources Researchmentioning
confidence: 99%
“…Several direct connections between algal blooms and causative factors have been recognized in previous research, including nutrient over-enrichment and undesirable hydrodynamic conditions. It is now broadly accepted among researchers that climate change has potential impacts, not only on water availability and hydrological risks (Jiang et al 2013a;van Vliet et al 2013), but also on physical, chemical, and biological processes in aquatic ecosystems, especially in eutrophic water bodies (Delpla et al 2009;Qin et al 2010;Islam et al 2012;Paerl & Paul 2012;Zhang et al 2012a;Park et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Process-based environmental models driven by data from general circulation models (GCMs) are another approach to explore the response of water quality to future climate (Komatsu et al 2007;Park et al 2013;van Vliet et al 2013). It is useful to investigate changes in a local water system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation